Care Experiences of Adults With a Dual Diagnosis and Their Family Caregivers. (20th July 2017) - Nicholas, David B.; Calhoun, Avery; McLaughlin, Anne Marie; Shankar, Janki; Kreitzer, Linda; Uzande, Masimba
Individuals diagnosed with developmental disability and mental illness (a "dual diagnosis") contend with multiple challenges and system-related barriers. Using an interpretive description approach, separate qualitative interviews were conducted with adults with a dual diagnosis ( n = 7) and their caregiving parents ( n = 8) to examine care-related experiences. Results indicate that individuals with a dual diagnosis and their families experience misunderstanding and stigma. Families provide informal complex care amid insufficient and uncoordinated services but are often excluded from formal care planning. A lack of available funding and services further impedes care. While negative care experiences are reported as prevalent, participants also describe instances of beneficial care. Overall, findings indicate a lack of sufficiently targeted resources, leaving families to absorb system-related care gaps. Recommendations include person- and family-centered care, navigation support, and capacity building. Prevention and emergency and crisis care services, along with housing, vocation, and other supports, are needed. Practice and research development regarding life span needs are recommended.